Strong chromatic index for multigraphs - Gvozdjak, Pavol; Horák, Peter; Meszka, Mariusz; Skupień, Zdzislaw (Utilitas Mathematica, 2000)
In this paper, multigraphs are a subject for the study of the strong chromatic index. In particular, we consider multigraphs whose underlying graph is a cycle, and investigate a strong chromatic index analogue of the chromatic index formula for such multigraphs.